Measuring the Extent of Iraqi Companies Commitment for Reporting Sustainability According to S & P / ISX / ESG & GRI Standards - Aljajawy, Talal; Al-Khafajy, Eman (The Arab Journal of Administration, 2020)
Sustainability deals with companies as a social unit that affects and is affected by society, so this society needs to know and transparently the social and environmental impacts as well as the economic impacts of corporate activities, So the most important global initiatives sustainability reporting is the global reporting initiative (GRI) is a nonprofit organization promotes economic, environmental and social sustainability and provides a comprehensive framework for reporting and reporting for all companies and institutions which is widely used throughout The world through the development and approval of initiative criteria to be applied on a consistent basis globally, providing a common language and unified way for businesses and stakeholders for corporate reporting and understanding the impact on the economy, environment and society, and to increase the quality and transparency of information to stakeholders, including future generations, Allowing for greater accountability and thereby provide stakeholders with the ability to identify and compare the effect of different companies. The aim of the research is to use GRI standards to analyze the content of the annual financial reports of a sample of listed companies in the Iraqi Stock Exchange to determine their commitment to reporting on their economic, environmental, and social and governance activities to achieve their responsibility towards society in accordance with the sustainable development perspective. In addition, the relationship of S & P reporting transparency to Iraqi listed companies on the Iraq Stock Exchange at the level of reporting on sustainability according to the GRI and ESG / ISX. The results of the study showed that the level of the Iraqi companies’ commitment to reporting on sustainability according to the GRI and ESG / ISX standards was weak and 29.10% for not reporting to most companies on the most indicators. In the S & P Transparency Index, the degree of transparency in the reporting was measured. The result was 39.53% resulting in weak contribution of Iraqi companies to the research sample in achieving sustainable development during the period (2015-2014).